Oral submucous fibrosis at pediatric age, now time to think: Series of two cases - Vinay K Gupta; Seema Malhotra; Ranjit Patil; Anurag Tripathi (Indian Journal of Medical and Paediatric Oncology)
The younger generation is consuming areca nut and areca nut products, which is coming in the market with different multicolored attractive pouches and easily available in each and every corner of the road. For the children from the lower socioeconomic strata, areca nut use is rampant. Alarmingly, it has been seen that the highest period of risk for engaging in areca nut alone is between the ages of 5 and 12. Oral submucous fibrosis associated with areca nut in children is a great concern for the Society and the Government. Factors associated with this report for consuming areca nut are levels of awareness, household environment, peer pressure, low cost, easy availability etc.